2003
DOI: 10.1002/chin.200301177
|View full text |Cite
|
Sign up to set email alerts
|

First Synthesis of (+)‐α‐ and (+)‐γ‐Polypodatetraenes.

Abstract: Terpenes Terpenes U 0200First Synthesis of (+)-α-and (+)-γ-Polypodatetraenes. -(KINOSHITA, M.; OHTSUKA, M.; NAKAMURA, D.; AKITA*, H.; Chem. Pharm. Bull. 50 (2002) 7, 930-934; Sch. Pharm. Sci., Toho Univ., Funabashi, Chiba 274, Japan; Eng.) -D. Singer 01-177

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Akita et al previously reported the total synthesis of (-)-drimenol based on enzymatic resolution [20], and in the same report, homodrimenol 124 was described as derived from drimenol. Starting from 124, Akita et al [61] carried out the first synthesis of (+)--polypodatetraene. The elongation of the carbon chain from the primary alcohol group of 124 was achieved by bromination and subsequent Drimenol: A versatile synthon Natural Product Communications Vol.…”
Section: Drimenol As Natural Chiral Synthon For Ambergris Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akita et al previously reported the total synthesis of (-)-drimenol based on enzymatic resolution [20], and in the same report, homodrimenol 124 was described as derived from drimenol. Starting from 124, Akita et al [61] carried out the first synthesis of (+)--polypodatetraene. The elongation of the carbon chain from the primary alcohol group of 124 was achieved by bromination and subsequent Drimenol: A versatile synthon Natural Product Communications Vol.…”
Section: Drimenol As Natural Chiral Synthon For Ambergris Related Compoundsmentioning
confidence: 99%
“…Hydroxylation at the 1 position is a distinctive characteristic of several natural bioactive terpenic compounds, such as forskolin (106) a potent inhibitor of adenylcyclase, mentioned before. Aranda et al [61] described that a simple reaction sequence can result, in few steps, in the preparation of 1α-hydroxylated compounds in good yields starting from 3β-hydroxy derivatives. The hemisynthesis of 1α-hydroxy drimenol involves the use of acetonide 83 previously reported [46], to protect and then regenerate, when appropriate, the 7,8-double bond.…”
Section: Drimenol In Microbiological Hydroxylationsmentioning
confidence: 99%
“…ました.16,18,19) これらの中に生理活性を有する化合物も多く,(8aS )-albaconol 20) と(-)-BE-40644 の 絶対構造は全合成することにより決定することがで きました. 21) 一方,(8aR )-24 からは(8aR )-copalic acid と(8aR)-copalol が合成されました(Fig. 6) . 17) 次 に 高 価 な 動 物 性 香 料 で あ る ( + ) -ambrein 27 (Fig.…”
unclassified